2022
DOI: 10.21608/bvmj.2022.129782.1509
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Hematological, Acute phase proteins and Radiographic changes in different respiratory affections in dogs and cats

Abstract: Respiratory affections are important clinical problems recorded in dogs and cats affecting their health condition. This study was carried out on a total of 84 animals including 32 dogs and 52 cats of both sexes and different breeds suffering from different respiratory affections including pneumonia, aspiration pneumonia, Feline upper respiratory diseases(FURD) and Canine infectious respiratory disease(CIRD). Clinical, hematological, biochemical and radiographic changes during these affections were evaluated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…In the present study, the most common clinical findings observed in dogs were analogous to Elgalfy et al (2022) [8] , Arsevska et al (2018) [2] , Ellis et al (2016) [9] , Sanchez-Viscaino et al (2016) [24] , Dear (2014) [7] , Ayodhya et al (2013) [3] , Vieson et al (2012) [26] and Peeters et al (2000) [19] . Whenever the causative organisms enter in to the respiratory tract by inhalation, they invade the mucosal layer and multiply in the epithelium.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, the most common clinical findings observed in dogs were analogous to Elgalfy et al (2022) [8] , Arsevska et al (2018) [2] , Ellis et al (2016) [9] , Sanchez-Viscaino et al (2016) [24] , Dear (2014) [7] , Ayodhya et al (2013) [3] , Vieson et al (2012) [26] and Peeters et al (2000) [19] . Whenever the causative organisms enter in to the respiratory tract by inhalation, they invade the mucosal layer and multiply in the epithelium.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, to evacuate the exudates from the tract cough is generated in the affected dogs. In the current study, different bacteria were isolated from the samples and similar observations were also recorded by various researchers Menard et al (2022) [14] , Moon et al (2022) [15] , Elgalfy et al (2022) [8] , Yadav et al (2020) [28] , Ayodhya et al (2013) [3] , Moonsun et al (2004) [16] , Moyaert et al (2019) [17] and Köse et al (2021) [11] . Staphylococcus spp., Escherichia coli and Bacillus spp.…”
Section: Discussionsupporting
confidence: 85%